Frequency dependent characteristics of an optically controlled InP MIS capacitor - Madheswaran M.; Chakrabarti P. (My University, 2025)
The paper reports the results of theoretical studies on the effect of intensity modulated illumination on the characteristics of a novel MIS capacitor which utilizes InP:Fe as the semiconductor substrate and Al2O3 as the insulator. The study reveals that the intensity modulated illumination causes significant changes in the characteristics of the device under illumination. The d.c. value of the capacitance depends on the peak value of the optical power while the fundamental component of the time varying capacitance of the device depends on the frequency of the signal modulating the intensity of the light. The semi-insulating nature of the semiconductor improves the photosensitivity of the device. A low value of the minority carrier lifetime enables the device to be used at higher frequencies compared to other MIS devices. The time varying capacitance of the device can be exploited for conversion of intensity modulated optical signal to frequency modulated electrical signal. Published by Elsevier Science Ltd. All rights reserved.